Analisis Pelanggaran Etika Pariwara Indonesia (EPI) dalam Iklan Sirup Marjan Versi Singabarong dan Kalana - Putri, Karen Elissa Anindya; Ananda, Salsabila; Amelia, Setia; Iswadi, Lailynisa Fadilla (Educationist: Journal of Educational and Cultural Studies, 2023)
Advertising is a form of communication about a product and/or brand to its target audience, so that they respond in accordance with the advertiser's objectives. Advertising is one of the places to disseminate information that must be considered, because this advertisement influences consumers. Sirup Marjan However, not a few business people who market their products by advertising and not following the Indonesian Advertising Ethics (EPI), one of which is the Singabarong and Kalana version of Sirup Marjan advertisements. The purpose of this study is to analyze the violation of the Indonesian Advertising Ethics (EPI) in the advertising of Sirup Marjan version of Singabarong and Kalana.